The PROFIT GROWTH, EARNING PERSISTENCE, INVESTMENT OPPORTUNITIES SET TERHADAP EARNING QUALITY DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI (Pada Perusahaan yang Terdaftar di JII 70 Periode 2020 - 2023) - Enggal, Enggal; Nena Arinta, Yusvita (EKOBIS, 2025)
This study aims to examine the effect of profit growth, earning persistence, and investment opportunities set on earning quality. The population used is companies listed on JII 70 for the 2020-2023 period. The population in this study amounted to 70 companies and the sample in this study amounted to 108 samples. The sample selection method used was purposive sampling. This study used a quantitative method with secondary data sources in the form of panel data obtained from the company's financial statements. Hypothesis testing in this study used regression linear tests with the help of the Eviews version 13 tool. The results of this study, that the profit growth and investment opportunities set variables have a positive and significant effect on earning quality. Meanwhile, earning persistence has no effect on earning quality. After adding the moderating variable firm size, that firm size strengthens the influence between profit growth and investment opportunities set on earning quality. Firm size cannot moderate the influence between earning persistence on earning quality.